THERAPEUTIC EFFECTS OF TRADITIONAL THAI MASSAGE ON CERVICAL RANGE OF MOTION, PAIN and ANXIETY IN PATIENTS WITH UPPER TRAPEZIUS MYOFASCIAL PAIN SYNDROME: AN ASSESSOR-BLIND RANDOMIZED CONTROLLED TRIAL - Buttagat, Vitsarut; Hancharoenkul, Benjamaporn (Archives of Allied Health Sciences, 2019)
Introduction: Myofascial pain syndrome (MPS) is one of the most common and painful conditions in chronic musculoskeletal syndrome which affects the muscle and its surrounding fascia. Although traditional Thai massage (TTM) has frequently been used as an alternative treatment for MPS, there is not enough evidence to support the effects of TTM on these patients. Purpose: To clarify the effect of TTM on cervical flexion, pain and anxiety in patients with upper trapezius myofascial trigger points. Method: Forty-eight patients were randomly assigned to receive a 30-minute session of either TTM (a form of deep massage with brief sustained pressure on the muscles along with passive stretching) or sham short wave diathermy (sham SWD) for 9 sessions over a period of 3 weeks. Thai Short-form McGill Pain Questionnaire (Th-SFMPQ), State Anxiety Inventory (STAI) and cervical flexion were measured before and 1 day after the treatment period. Results: TTM group showed a significant improvement in all parameters after 3 weeks of the treatments whereas, the sham SWD group showed a significant improvement only in the Th-SFMPQ and STAI (p < 0.05) (paired t-test). Moreover, the TTM group demonstrated more improvement than the sham SWD group in all parameters at the end of the treatments (p <0.05) (ANCOVA). Conclusions: TTM appears to be a useful method of reducing pain and anxiety and increasing cervical flexion in this patient population.